Motivation of Sugar Palm Sugar Processors in Wolo Subdistrict, Kolaka Regency, Southeast Sulawesi, Indonesia - Edi Syah Mihrad (International journal of technology and education research, 2025)
This study aims to analyze the motivation of palm sugar processors in Wolo District, Kolaka Regency, Southeast Sulawesi. The research was conducted using a descriptive analysis approach, with data collected through surveys and interviews with 60 palm sugar processors. The results show that the majority of palm sugar processors have low motivation (68.33%), with economic motives being the most dominant factor influencing their motivation. The study also highlights the importance of improving the motivation of palm sugar processors through government intervention, training, and the development of cooperative networks to enhance the sustainability and productivity of the palm sugar industry. This research contributes to the understanding of the factors influencing the motivation of small-scale agro-industry workers and provides recommendations for policymakers and stakeholders in the palm sugar industry